FABRICATION OF CHITOSAN BIOPOLYMER FROM PEARL OYSTER SHELLS (Pinctada maxima) FOR MEDICAL APPLICATIONS - Nurmaulida, Siti Ema; Alawiyah, Geby; rahayu, Susi; Taufik S, Ahmad; Hidayatullah, Kholik; Kurniawidi, Dian W.; Ali, Muhamad (Universitas Mataram, 2023)
Chitosan is one of the biopolymers that has recently been developed in the medical field. Chitosan is biocompatible, biodegradable, and non-toxic, so it is safe for the human body. This study aimed to identify the characteristics of chitosan isolated from pearl oyster shells. Chitosan is obtained through three stages: deproteination, demineralization, and deacetylation. Characterization of chitosan is done physically and chemically including organoleptic test, yield calculation in each step of isolation, FTIR, and XRD. Isolated chitosan identified deacetylation degree and functional group with FTIR. While the crystal structure was determined using XRD. The results showed that chitosan powder has a beige color with a final yield of 7,06%. The characterization of FTIR shows that synthesized pearl oyster shells have successfully formed chitosan compounds with a deacetylation degree of 81,50%. Another characteristic is the crystal structure obtained; chitosan has orthorhombic unit cells with a degree of chitosan crystallinity of 36,94%. Based on the result, chitosan has met several standards in medical applications as a biomaterial.